Il Terzo Settore alla prova dell'accoglienza. percorsi degli immigrati nella Regione Calabria (Società e diritti, 2024)
In this contribution the Author takes into consideration the application of the new tools of shared administration provided by the Third Sector Code, analysing the reality in region Calabria with reference to the reception of immigrants. The study confirms that the principle of “horizontal subsidiarity”, recognised in Italy at the constitutional level, could be the most suitable to orient the dynamics of legislation and administration in addressing emerging problems such as immigration through the integration of ETS(Third Sector Bodie